Contrasting responses to Pleistocene climate changes: a case study of two sister species Allium cyathophorum and A. spicata (Amaryllidaceae) distributed in the eastern and western Qinghai–Tibet Plateau. Issue 7 (10th March 2015) - Wang, Xinyu; Li, Yuanshuo; Liang, Qianlong; Zhang, Lei; Wang, Qian; Hu, Huan; Sun, Yongshuai
Abstract It has been hypothesized that species occurring in the eastern and the western Qinghai–Tibet Plateau (QTP) responded differently to climate changes during the Pleistocene. Here, we test this hypothesis by phylogeographic analysis of two sister species, Allium cyathophorum and A. spicata. We sequenced two chloroplast DNA (cpDNA) fragments (accD‐psaI and the rpl16 intron) of 150 individuals, and the nuclear (ITS) region of 114 individuals, from 19 populations throughout the distributional ranges of these species. The divergence between the two species was dated at 779 ‐ 714 thousand years before the present and was likely initiated by the most major glaciation in the QTP. Analysis of chlorotype diversity showed that A. spicata, the species occurring in the western QTP, contains much lower genetic diversity (0.25) than A. cyathophorum (0.93), which is distributed in the eastern QTP. Moreover, multiple independent tests suggested that the A. spicata population had expanded recently, while no such expansion was detected in A. cyathophorum, indicating a contrasting pattern of responses to Pleistocene climate changes. These findings highlight the importance of geographical topography in determining how species responded to the climate changes that took place in the QTP during the Pleistocene.